Academic Information System Design Blockchain Based College: Desain Sistem Informasi Akademik Perguruan Tinggi Berbasis Blockchain - Alvian Abdul Jabar; Irman Hermadi; Yandra Arkeman (Universitas Singaperbangsa Karawang, 2021)
Academic Information System (SIAKAD) is an application designed for data management purposes sothat the entire process of academic activities can be managed into useful information. This data isstored in a database, this causes problems, namely the difficulty of backing up data in case of damageand difficulty when validating data because there is no verifier when inputting data, one of the datastored is student transcripts, as we know that transcripts This student score can be used for scholarshiprequirements and applying for jobs so that the transcript must be authenticated. Therefore, the purposeof this research is to design a blockchain-based SIAKAD application that can make it easier to checkdata validation to prove the authenticity of student grade transcripts and display traceability of studentgrade data. Blockchain technology is a ledger that will record all activities carried out then the datawill be distributed to each node that has been determined and already has a certificate authority toaccess the blockchain, then each node will have a copy of each transaction, each transaction will beinterrelated with the transaction next. The transactions made are student value data, the data will bestored into the blockchain. In this study, a blockchain-based academic information system applicationhas been designed using the prototyping method and then using the hyperledger fabric as a frameworkfor building blockchain. The result of this research is a blockchain information system application thatcan verify the authenticity of grade transcripts and see traceability of student grade data.